Discerning the Difference Between Lumens and Scalariform Perforation Plates in Impeding Water Flow in Single Xylem Vessels and Vessel Networks in Cotton - Gao, Yang; Yang, Zhenjun; Wang, Guangshuai; Sun, Jingsheng; Zhang, Xiaoxian (Frontiers in Plant Science, 2020)
The geometrical structure and spatial arrangement of lumens and perforation plates in xylem vessel modulate water flow from root to leave. Understanding their respective hydraulic functions is essential to unveil how plant regulates its hydraulic network to facilitate the ascent of sap under biotic and abiotic stress but is challenging because of the opaque nature of the vessel network and water flow within it. We made the first-ever effort to discern the difference between lumens and perforation plates in impeding water flow in single vessel and vessel network using x-ray tomography and pore-scale numerical simulation. Three-dimensional structures of xylem vessels in stem of two cotton cultivars were acquired non-invasively using x-ray tomography at high spatial resolution, and a lattice Boltzmann model was developed to simulate water flow through the xylem networks at micron scale. The detailed water velocity and pressure simulated using the model were used to calculate the hydraulic resistance caused by each lumen and perforation plate in individual vessels. The results showed that the hydraulic resistance spikes whenever water flows across a perforation plate, and that the overall hydraulic resistance caused by perforation plates in individual vessel accounts for approximately 54% of the total resistance. We also calculated the hydraulic conductance of individual vessel and vessel network using the simulated water velocity and pressure at micron scale and compared it with those estimated from the Hagen Poiseulle (HP) equation as commonly used in the literature by assuming the xylem vessels as isolated tubes. While it was found that the HP equation overestimated the hydraulic conductance by more than 200%, the overestimate was largely due to the incapability of the HP equation to represent the perforation plates rather than its approximation of the irregular vessels by circular tubes.